A study on ambulance response time in Kuala Lumpur, Malaysia - Sujak, Ahmad Fadzil (2008)
Introduction: Ambulance service is a main part of pre hospital treatment. Time taken to response to emergency call is known to impact on the chain of survival. Ministry of health (MOH), Malaysia targeted 95% of the ambulances arrive at the scene of the incident within 30 minutes of received of the emergency call. Objectives: To study the performance of emergency ambulance service based on ambulance response time in Kuala Lumpur, by analyzing the call processing time and dispatch-to-scene time. Methodology: A retrospective study was conducted at the Medical Emergency Call centre (MECC), Hospital Kuala Lumpur (HKL) from October I st 2007 until April 31st 2008. The study was sent to National Medical Research Registration MOH Malaysia for approval. All emergency calls for ambulance service were handled by call taker in MECC, HKL. The call taker would interact with the caller to gather critical medical information through an algorithmic set of questions as depicted in Emergency dispatch form and would manually filled up the form. The call taker would determined appropriate medical call triage according to the information collected. With all the gathered information from caller, then the call taker pass it to the call dispatcher in MECC, HKL with the exact time being recorded. Then the call dispatcher ordered the responder for ambulance deployment, and the time the responder receiving order from the call dispatcher recorded. The responder would make a decision of the appropriate type (Basic or Advanced) of ambulance team to be deployed. Subsequently, the call dispatcher would obtain from the responder the time of ambulance arrival at the scene or incident site. After completion, the 'Emergency Dispatch Form' was then collected and was kept in the MECC room at HKL. Results: A total of 525 calls were included in the study and entered for data analysis. 327 of cases involved non trauma patients and the remaining 198 numbers of cases comprised of trauma patients. In this study it was demonstrated that 87.8% (n=461) of the cases had a time period of being less than 5 minutes from when the calls were picked up, information obtained and phone triage done until the time responders were activated. Meanwhile 12.2% (64) of cases had registered times of more than 5 minutes. In this study, the dispatch-to-scene time has a mean of21.9 minutes with standard deviation of 14.9. Although trauma-type calls formed only 37.7% of the calls studied, they showed higher percentages (86.4%) of achieving ART within 30 minutes as compared with non trauma-type of calls which formed 62.3% of cases and yet only 78.3% achieved ART within 30 minutes. The difference of 8.1% was observed and it was statistically significant. Conclusion: This study shows that the performance of ambulance service in Kuala Lumpur was still below than expected by the MOH Malaysia Guideline standard. The achievements by components were for 'call processing time' was 87.8% and 86.4% for the 'dispatch-to-scene time' was 86.4% (trauma calls). Location of patients or incident site did play a significant role in determining the outcome of the ambulance response time. Well link roadways in Kuala Lumpur help emergency responders to attend motor vehicle accidents promptly. The use of either hospital based or NGO based emergency services did not affect the ambulance response time significantly.